(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The development and formation of the European detective genre were deeply influenced by the social and cultural conditions of the nineteenth century. The rapid industrial revolution and urbanization across Europe led to the emergence of new societal problems, which were reflected in literature through the themes of crime and morality.[1] The main purpose of detective fiction in European literature, according to many scholars, is not only to solve a crime but also to reveal issues of social injustice, moral dilemmas, and the complexity of human nature. As the British scholar S. Chandler emphasized in his essay “The Simple Art of Murder”, “A detective story is not merely about solving a mystery, but about exposing the inner unrest of society and the dark sides of the human soul.”[2].